Vascular Thoracic Outlet Syndrome: Experiences at the National Institute of Cardiovascular Diseases, Dhaka - Hossain, MF; Sarker, SR; Sabah, MN; Bashar, AHM; Dey, NK; Hakim, E; Hossain, GMM; Mandal, NC (Cardiovascular Journal, 2018)
Background: To analyze our recent experiences at the National Institute of Cardiovascular Diseases (NICVD) with the management of vascular Thoracic Outlet Syndrome (TOS). Methods: Retrospective review identified 51 patients (age range 23 to 67 years) with vascular TOS, among them 47 patients with arterial type TOS underwent surgical treatment from January 2012 to December 2015. Evaluation included clinical assessment plus duplex ultrasonography and contrast arteriography and outcome of treatment. Results: In 44 (94%) patients, surgery was successful in relieving the ischemic symptoms. Major amputations could be avoided in 21 of the 28 patients presenting with gangrene. Recurrent thrombo-embolism of the distal arterial tree was found in 5 patients requiring repeat embolectomy. At one year follow-up, 73% of the patients remained free from ischemic upper limb symptoms. Conclusions: Though relatively uncommon, arterial TOS is a potentially limb threatening condition. Early detection of the anatomical abnormality with its surgical correction is required to avoid major complications. Cardiovasc. j. 2018; 11(1): 50-52